The Effectiveness of The Origami Model In The Achievement of Fifth-Grade Science Students In Physics And Their Tendencies Towards It (Journal of the College of Basic Education, 2026)
The study aims to determine the effectiveness of the Origami model on the achievement and attitudes of fifth-grade science students in physics.This was verified through the following hypothesis:-At the statistical significance level (0.05), the results showed no statistically significant differences between the average achievement scores of students in the experimental group, who were taught using the Origami model, and the average achievement scores of students in the control group, who were taught using the traditional method, on the physics achievement test.- At the statistical significance level (0.05), the results showed no statistically significant differences between the average achievement scores of students in the experimental group, who were taught using the Origami model, and the average achievement scores of students in the control group, who were taught using the traditional method, on the physics attitude test. The research community was determined by the fifth-grade science students at Al-Batoul Girls’ Secondary School, who were chosen intentionally, for the academic year (2025-2026) AD, numbering (158) students distributed among six study sections (A, B, C, D, E, and F). The researcher used the experimental design with two groups, experimental and control, one of which partially controls the other, and from those with a post-test, by random assignment, the two sections (E and F) were chosen as the research groups, as they were determined in order, experimental and control. The number of students was (62), and after statistically excluding the students who failed in the two groups (3, 4) students, the research sample became composed of (55) students, with (27) students for the experimental group and (28) students for the control group. The two groups were rewarded in variables (age in months, intelligence, previous information in physics, achievement in physics from the previous grade). The scientific material was determined in the first five chapters of the physics book for the fifth scientific grade, which was scheduled for the first semester of the academic year (2025-2026) AD. The researcher taught the two research groups herself, as she formulated the behavioral objectives for the five chapters, and their number reached (106) behavioral objectives representing the six levels of Bloom’s classification of the cognitive domain, respectively (remembering, comprehension, application, analysis, synthesis, evaluation). She prepared the necessary teaching plans for that, as they amounted to (23) plans for the experimental group according to the steps of the Origami model, and the same for the control group according to the usual method. Two models of both plans were presented to the judges to ensure they accurately represented the content, steps of the Origami model, and the traditional method. As for the research tools, the researcher prepared an achievement test consisting of (40 test paragraphs), including (30) paragraphs of the objective question type because they have a high degree of stability and are not affected by the subjectivity of the corrector, (7) of them are essays with a short answer, and finally (3) paragraphs representing problems, and she confirmed its validity, and according to the stability coefficient, the agreement rate was (84%). She also built a scale of tendencies towards the subject, which may have been (32) paragraphs with five graded alternatives to answer the paragraphs of the scale, which are (always, often, sometimes, rarely, does not apply to me), and (4) paragraphs revealing to get rid of the state of mental preparation among the students, represented by paragraphs (8, 15, 23, 31). The scale was presented to a group of experts and arbitrators, and the agreement rate was (80%), and the scale was considered valid. The results were in favour of the experimental group that was studied according to the Origami model in the achievement test. And the scale of tendencies. From these results, the researcher concluded that teaching using the Origami model has a significant impact on increasing students’ achievement and improving their tendencies towards the subject. In light of this, a number of recommendations and proposals were made related to the research results.